2018
DOI: 10.1108/ijem-02-2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

Management accounting practices, governing boards and competitive advantage of Ugandan secondary schools

Abstract: Purpose-This paper reports on the results of a study carried out to determine the use of Management Accounting Practices (MAPR) in Ugandan secondary schools. The study also sought to determine whether MAPR and governing boards (board size, gender diversity and frequency of board meetings) influence the perceived competitive advantage. Design/methodology/approach-This study is cross-sectional and correlational. Data were collected through a questionnaire survey of 200 secondary schools. The data was analysed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…According to Tusiime et al (2011), ownership structure is positively associated with performance of firms. Further, Nkundabanyanga et al (2018) found that ownership is positively associated with competitive advantage of a firm. For capital structure, increased debts in a firm increases monitoring costs (Bekiaris et al , 2014; Jensen and Meckling, 1976) since shareholders want to be aware on how debt finances have been utilized or invested (see Table II for variable measurement).…”
Section: Methodsmentioning
confidence: 97%
“…According to Tusiime et al (2011), ownership structure is positively associated with performance of firms. Further, Nkundabanyanga et al (2018) found that ownership is positively associated with competitive advantage of a firm. For capital structure, increased debts in a firm increases monitoring costs (Bekiaris et al , 2014; Jensen and Meckling, 1976) since shareholders want to be aware on how debt finances have been utilized or invested (see Table II for variable measurement).…”
Section: Methodsmentioning
confidence: 97%
“…Tusiime et al (2011) found that ownership structure is positively associated with performance of firms. Further, Nkundabanyanga et al (2018) found that ownership is positively associated with competitive advantage of a firm. For capital structure, increased debts in a firm increase monitoring costs (Bekiaris et al , 2014; Jensen and Meckling, 1976) since shareholders desire to remain informed on how debt finances have been utilized or invested.…”
Section: Methodsmentioning
confidence: 97%
“…In addition, there are several control variables added in this study, namely firm age, board size, board meeting and tangibility. These variables were recommended by previous studies because they can affect firm performance (Eluyela et al, 2018;Mallinguh et al, 2020;Mubeen et al, 2020;Pucheta-Martínez & Gallego-Álvarez, 2020;Vu et al, 2019), but the use of these variables is still limited in research on competitive advantage (Jeong & Chung, 2022;Lu et al, 2021;Nkundabanyanga et al, 2018;Nyuur et al, 2019;Whitler & Puto, 2020). This is quantitative research and uses secondary data.…”
Section: Methodsmentioning
confidence: 99%